ANALISIS PERMINTAAN PRODUK NUTRISI SHAKE MIX DARI HERBALIFE DI KOTA PEKANBARU - William Silitonga; Zulkarnaini '; Hendro Ekwarso (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted to determine the factors that influence the demand of nutrition product Shake Mix from Herbalife among reproductive age consumers in Pekanbaru city. The data used in this research is primary and secondary data. Using descriptive data analysis methods. The population in this research is peoples on productive age who consume Shake Mix sampled 100 respondents using the Slovin formula. The result of this research showed that the factors that influence the demand of Shake Mix from Herbalife is the ability or efficacy of the product, affordable prices and interesting flavors.Keywords : demands, nutrition, Herbalife, Shake Mix, diet, price